Tourists' perceptions of non-human species in zoos: An animal rights perspective - Christou, Prokopis A.; Nikiforou, Elena S. (My University, 2021)
This qualitative study aims to reveal tourists' perceptions of non-human species in zoos while adopting an animal rights perspective. Study findings indicate that tourists are concerned about the well-being of animals that are kept in zoos and conceive that animals in zoos are distressed and “unhappy”. Yet, they value the outcome of their zoo experience and interaction with animals, thus continue to visit zoos for leisure/educational purposes. The study's findings enable the conceptualisation of zoos, their societal impact, tourists' concerns about animals kept in zoos and the need of tourism stakeholders to transform zoos.
Keywords: Animals; Tourists' perceptions; Zoos